Scorpion Stings in Saudi Arabia: An Overview - Alhamoud, Mustafa A.; Al Fehaid, Mohammad S.; Alhamoud, Mohammed A.; Alkhalifah, Ahmed A.; Alzoayed, Mohammed H.; Menezes, Ritesh G. (Acta Biomedica Atenei Parmensis, 2021)
Background: Scorpion envenomation is an important cause of morbidity and mortality, especially in children and elderly worldwide. In Saudi Arabia it is an important issue as the climate and the desert terrain are ideal for scorpions’ habitat. Methods: A literature review of articles on the incidence of scorpion stings in Saudi Arabia. Results: In Saudi Arabia, 28 species of scorpions were identified. Approximately 14,500 scorpion stings are annually reported, with full recovery and low morbidity and mortality rates. The highest risk groups to get envenomated are people living in the desert. And the highest incidence of scorpion stings was during the summer season. Conclusion: The number of scorpion stings in Saudi Arabia is considerable and there were insufficient studies regarding such topic. The aim of this study is to emphasize on the importance of scorpion stings in Saudi Arabia and providing updates regarding scorpion types, clinical presentations, and statistical data.